Affect role conflict, role ambiguity and work stress on performance of government employees local secretariat government kerinci district - Ronal Regen; Evi Azrianto; Addrian Rolyes; Al Ikhwan Setiadi; Dedi Iryanto (Education and Social Sciences Review, 2022)
This study aims to see the effect of (1) role conflict on the performance of the administrative division of the Kerinci District Secretariat (2) Role ambiguity on the performance of employees of the Kerinci District Secretariat of Governance Section (3) Work stress on employee performance in the Governance Section of the Regional Secretariat of Kerinci Regency (4) Role conflict, role ambiguity and work stress have a joint effect on the performance of the employees of the Kerinci District Secretariat Governance Section. The population and sample in this study were all 35 employees of the Administration of the Regional Secretariat of Kerinci Regency. The technique of determining the number of samples using total sampling. The data analysis technique used multiple regression by fulfilling the requirements of the classical assumption test of normality, and multicollinearity, heteroscedasticity. Resultsthis study shows that (1) role conflicthas a negative significant effect on the performance of the employees of the Governance Section of the Regional Secretariat of Kerinci Regency (2) Role ambiguityhas a significant negative effect on the performance of the employees of the Governance Section of the Regional Secretariat of Kerinci Regency (3) Work stresshas a significant negative effect on the performance of the employees of the Governance Section of the Regional Secretariat of Kerinci Regency (4) Role conflict, role ambiguity and job stressjointly have a positive effect on the performance of the employees of the Kerinci District Secretariat of Governance Section.